1983
DOI: 10.1093/jn/113.10.1972
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Mitochondrial Integrity in the Pancreas of the Chick

Abstract: The activity of selenium-dependent glutathione peroxidase (SeGSH-Px) in the pancreas was found to decline in response to Se depletion in the chick at approximately the same time as the appearance of histopathological changes in the acinar cells of the pancreas, indicative of the onset of nutritional pancreatic atrophy. Oral administration of 10 micrograms of Se as Na2SeO3 to Se-deficient chicks increased SeGSH-Px activity in liver and plasma within 12 hours but not in pancreas until 36 hours. Histological sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Selenium is also an essential element and component of the mitochondrial protein, glutathione peroxidase (Levander et al, 1974). Several reports have shown that selenium deficiency causes defects in mitochondrial structure, integrity, and electron transport chain function (Whitacre and Combs, 1983;Sokolove et al, 1993;Rani and Lalitha, 1996). The loss of antioxidant capacity of the mitochondria due to reduced glutathione peroxidase activity is the likely etiology.…”
Section: Metals Necessary For Mitochondria Not Used Directly In the Hmentioning
confidence: 99%
“…Selenium is also an essential element and component of the mitochondrial protein, glutathione peroxidase (Levander et al, 1974). Several reports have shown that selenium deficiency causes defects in mitochondrial structure, integrity, and electron transport chain function (Whitacre and Combs, 1983;Sokolove et al, 1993;Rani and Lalitha, 1996). The loss of antioxidant capacity of the mitochondria due to reduced glutathione peroxidase activity is the likely etiology.…”
Section: Metals Necessary For Mitochondria Not Used Directly In the Hmentioning
confidence: 99%
“…However, the pancreas of chickens is a major target organ of Se deficiency [16,17]. Thompson and Scott (1970) reported that diets extremely deficient in Se produced severe pancreatic degeneration in chicks [18].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these findings, they suggested that the primary metabolic lesion in severe Se deficiency may be the loss of mitochondrial integrity due to diminished antioxidant protection via SeGSHpx in the cytosol and mitochondria1 matrix space. Whitacre and Combs (7) supported their hypothesis with limited observations of pancreatic acinar ultrastructure using transmission electron microscopy which they interpreted as showing both loss of ER and mitochondria1 disruption in affected cells.…”
mentioning
confidence: 78%
“…Noguchi et al (6) found that atrophied pancreases from Se-deficient chicks contained reduced amounts of zymogen. In subsequent work, the respiratory function of mitochondria isolated from Se-deficient chicks with early-stage pancreatic atrophy (i.e., without fibrosis) was found to be normal (3,7); however, the yield of mitochondria from Se-deficient pancreases was only 72% of that of Se-adequate controls (7). Whitacre and Combs (7) found that early-stage Se-deficiency involved marked reductions in the synthesis of RNA and protein in the pancreas (but not in the liver).…”
mentioning
confidence: 99%
See 1 more Smart Citation